Expect the unexpected: presenting research leads to unforeseen gains. (11th September 2019) - Lane, Dan
Abstract : Dan Lane is a first year PhD student at the University of Leicester, developing biochemical methods in non-adherence testing alongside Leicester Diabetes Centre. A pilot study he helped to conduct prior to the start of his postgraduate degree was accepted by Diabetes UK and so, with the help of a travel grant from the Biochemical Society, he travelled to Liverpool to present his work. The Biochemical Society provides General Travel Grants to support attendance at scientific meetings, training events or any other event relevant to your career. Postgraduate, Early Career, Full and Emeritus Members are encouraged to apply to further their lifelong learning.